Protective effect of vasostatin-1 plasmid-like nanoparticles on aortic aneurysm and its mechanism. Issue 1 (1st January 2022) - Wang, Pingshan; Wang, Wei; Peng, Xingxing; Ruan, Fugui; Yang, Shiyao
ABSTRACT: Vasostatin 1 (VS-1) plays an important role in the regulation of various tissue injury and repair processes, but its role in aortic aneurysm remains unclear. The plasmid-like nanoparticles containing the vasostatin-1 gene Pul-PGEA-pCas-sgVs-1 were constructed, and their guarantee, safety, hemolysis, and particle size were analyzed. Eighty-four eight-week-old male ApoE-mice were randomly divided into blank group (without any treatment), model group (Ang II aortic aneurysm model + tail injection of PBS), control group (modeling + tail injection of Pul-PGEA-pCas9), and experimental group (modeling + tail injection of Pul-PGEA-pCas-sgVs-1), with 21 rats in each group. The incidence, mortality, and maximum diameter of abdominal aortic aneurysm (AAA) and the contents of high sensitivity C-reactive protein (HS-CRP), soluble intercellular adhesion molecule-1 (ICAM-1), soluble vascular cell adhesion molecule-1 (VCAM-1), and TNF-a in serum were compared in different groups of mice. The results showed that Pul-PGEA-pCas-sgVs-1 had good biosafety and transfection ability. The maximum diameter of abdominal aorta, incidence of abdominal aortic aneurysm, mortality, and the expression levels of HS-CRP, ICAM-1, VCAM-1, and TNF-a in the experimental group were lower than those in the model group ( P < 0.05). These results indicated that the plasmid-like nanoparticles Pul-PGEA-pCas-sgVs-1 can inhibit the development of aorta by down-regulating the expression of inflammatory factors, which played a good protective role on the aorta. Graphical abstract: uf0001